Efficacy and Safety of Carbetocin for the Prevention of Primary PPH During Caesarean Section: An Open Label Single Arm Study - RAZZAQUE, S; KHAN, AD (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: The risk of postpartum haemorrhage is much higher for women undergoingcaesarean section, particularly in developing countries where the majority of operations arecarried out as an emergency procedure. Postpartum haemorrhage is the leading cause ofmaternal mortality worldwide. Around 67–80% of cases are caused by uterine atony.Preventive measures include prophylactic drugs use to aid uterine contraction after delivery,thus avoiding severe blood loss and reducing maternal morbidity and mortality. Carbetocin asynthetic analogue of oxytocin is currently indicated for prevention of uterine atony afterdelivery by caesarean section in spinal or epidural anaesthesia. The Aim of Study: To see the efficacy and safety of Carbetocin for the prophylaxis of PPHduring caesarean section.Patients and Methods: An open label single arm clinical trial was conducted in the BagerhatSadar Hospital, Bangladesh over a period of six months from May 2017 to October 2017.Ninety patients who had got admitted in Bagerhat Sadar Hospital, undergoing cesareansection at term were selected. Each patient obtained a single dose of 100 microgramcarbetocin intravenously during cesarean section, immediately after the delivery of the babyand prior to the delivery of the placenta. Outcome measures such as primary PPH, bloodloss was observed and measured by weighing sanitary napkin observed for six hours. Needfor additional uterotonic drug, additional blood transfusion as well as adverse effects were alldocumented. Results: Massive blood loss occurred only in 3.3% patients. Among the study population96.7% patients did not need any additional uterotonics. No patient had developed fever,arrhythmia, pulmonary edema, tremor, abdominal pain and pruritus. Only 2.2% had nausea,only 3.3% had hypotention, only 3.3% had vomiting and only 2.2% had headache which wasnot statistically significant. Only 4.4% patients developed PPH. Conclusion: Carbetocin appears to be an effective new drug for the prophylaxis of postpartumhemorrhage in cesarean section. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 119-124